"…they didn't just do it because it was a job": Representing wardens in Canadian penal history museums. (June 2018) - Walby, Kevin; Piché, Justin; Friesen, Bethany
Abstract: Wardens figure centrally as part of the plot in popular culture representations of prisons such as in films (e.g. The Shawshank Redemption ) and television (e.g. Wentworth ). Yet little is known about how wardens are depicted in another form of criminal justice popular culture: the penal history museum. This paper examines representations of wardens observed as part of a study of 45 punishment memorialization sites across Canada. We analyze the symbolism used in these penal history museums, as well as the framing used to curate warden-related objects. Our analysis reveals that positive representations of prison wardens depict them as family-oriented, benevolent men of a strong character, who embody and command respect for authority. We found fewer representations that were critical of warden's work. We conclude by reflecting on the implications of our findings for literature on cultural depictions of penality and justice.